Seroconversion to Lutzomyia intermedia LinB-13 as a biomarker for developing cutaneous leishmaniasis - Augusto M. Carvalho (Nature Portfolio, 2017)
Abstract Sand flies inject saliva while feeding in the vertebrate host and anti-saliva antibodies can be used as biomarkers of exposure to Leishmania vectors. We expressed recombinant salivary proteins from Lutzomyia intermedia, a vector of Leishmania braziliensis, and evaluated the seroreactivity in exposed individuals in search for exposure markers. We found a strong correlation among positive serology to recombinant proteins LinB-13, 26, 15, 21 and to salivary proteins: rLinB-13 was the top performing molecule; IgG4 was the most predominant antibody subclass and antibodies to rLinB-13 did not cross react with Lu. longipalpis salivary proteins. By evaluating a cohort of contacts of CL patients, we confirmed that rLinB-13, an antigen 5-related protein, is a marker of exposure to Lu. intermedia with high degree of accuracy. In a 5-year follow up, we determined that individuals who developed CL presented higher anti-rLinB13 IgG responses, before the appearance of clinical symptoms. They also presented a lower frequency of cellular responses to the parasite (DTH). Our results show that seroconversion to a salivary molecule, rLinB-13, is a marker of risk for CL development caused by Leishmania braziliensis. This highlight the possibility of developing tools based on vector molecules to manage the disease in endemic areas.